Challenges to the creator doctrine : authorship, copyright ownership and the exploitation of creative works in the Netherlands, Germany and the United States /: authorship, copyright ownership and the exploitation of creative works in the Netherlands, Germany and the United States. (1994) - Unknown
No abstract available